THE INSERTION OF ENGLISH LANGUAGE IN THE CURRICULUM OF THE INITIAL GRADES IN BRAZILIAN SCHOOLS - Scaglion, Luiz Fernando [UNESP]; Araujo, Luciana Aparecida de [UNESP]; Mosca Giroto, Claudia Regina [UNESP] (Unesp-faculdade Ciencias & Letras, 2019)
English language learning should not be reserved only for a small part of society, but it must be a guaranteed right to all and provided by the State, considering the expansion of communication and work possibilities. Given the relevance of this theme, the present study aimed to analyze the studies that discussed the insertion of the English language in the curriculum of the initial grades of Elementary School from 1996 to 2018 available in the Digital Library of Theses and Dissertations (BDTD). It reached the conclusion that from 1808 until the twentieth century, English has been a language for the elite and politically the language was not considered necessary for the training of workers. Although educational changes currently guarantee the teaching of this language in public schools, there is evidence of the necessity for greater investments in education and teacher training to ensure access and quality teaching of this language.
Keywords: English language; Curriculum; Initial grades